2017
DOI: 10.1186/s13256-017-1223-5
|View full text |Cite
|
Sign up to set email alerts
|

A rare presentation of myxofibrosarcoma as a Pancoast tumor: a case report

Abstract: BackgroundMyxofibrosarcoma is an aggressive soft tissue neoplasm, classified as a variant of malignant fibrous histiocytoma. Most often, it occurs in middle to late adult life peaking in the seventh decade and involving the lower extremities (77%), trunk (12%), and retroperitoneum or mediastinum (8%). We report the first case of thoracic myxofibrosarcoma presenting as a Pancoast tumor.Case presentationA 48-year-old non-tobacco smoking African-American man presented with a slow-growing mass in his neck along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…In this paper, despite other studies (1,3,8) for the first time, immunohistochemical staining was negative for CD34 in this type of cancer after twice repeated.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…In this paper, despite other studies (1,3,8) for the first time, immunohistochemical staining was negative for CD34 in this type of cancer after twice repeated.…”
Section: Discussioncontrasting
confidence: 65%
“…Myxofibrosarcoma is a kind of soft tissue sarcoma (STS) that one of the most common neoplasms of the limbs of elderly patients reported in the 1970 th (1). Although both genders are involved, the prevalence of myxofibrosarcoma among males is higher than females.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bethel et al reported the case of a giant myxofibrosarcoma involving the brachial plexus and causing compression of the airway structures [ 36 ]. An interesting case of MFS presented a Pancoast tumor-like manifestation with upper extremity pain, hand muscle atrophy, and Horner`s syndrome [ 37 ]. It can also present as pain in the knee joint [ 38 ].…”
Section: Discussionmentioning
confidence: 99%